Analysis Of The Effectiveness Of Infiltration Wells In Disaster Risk Reduction: Literature Study - Yoga Aztrianto; Syamsul Maarif; Lilik Kurniawan; Setyo Aji Pramono (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
Infiltration wells are wells or holes located on the surface of the ground. The rapid urban development has led to a decreasing area of rainwater infiltration, as the increasing coverage of buildings reduces the open space and results in longer accumulation times for water, potentially causing flood disasters. Aside from flooding issues, the availability of groundwater is crucial for the areas where rainwater infiltration occurs. If groundwater decreases, the supply of groundwater will be affected, impacting communities whose clean water needs depend on groundwater in their region. The research method used in this study is an internet-based literature review. Downloaded articles are then imported into Nvivo 12 Plus software. The data is examined and analyzed to draw conclusions. Based on the analysis of the five articles, the author concludes that infiltration wells are effective in reducing disaster risks. Additionally, infiltration wells can be used as a substitute for groundwater and enable communities to adapt to climate change. Efforts from all layers of society are essential to create infiltration wells in their respective areas because infiltration wells are not meaningful if only a few communities implement them.